Kuhn-Tucker conditions and linear homogeneity - Max Albert (Universität Konstanz, Sonderforschungsbereich 178 - Internationalisierung der Wirtschaft, 1994)
The paper proves a theorem on modified Kuhn-Tucker conditions for the case where a linearly homogenous function is part of the target function. These conditions are necessary and sufficient if target function and constraints satisfy certain re-quirements. Moreover, the envelope theorem can be applied as if the Standard Kuhn-Tucker conditions were valid. An application to a problem in the theory of production illustrates the usefulness of the theorem.
Keywords: 330